Studies on Chemical Availabilities of Inorganic Phosphorus Fractions and Their Distribution in Various Soils Separates in Soils of Rajasthan - Singh, P; Seth, S P (Annals of Arid Zone, 2016)
Organic and inorganic phosphorus in sixteen soils of Rajasthan from distinctly separated places -representing different soil textures are reported. The inorganic form of phosphorus was further fractionated into adsorbed aluminium, iron and calcium bound forms. Available phosphorus was also determined by Olsen's, Morgan's and Bray's procedures. Phosphnrus extracted by Olsen's procedure correlates significantly with different fractions of inorganic phosphorus and organic phosphorus. It, therefore, can be recommended for determining available phosphorus in Rajasthan soils. The organic fractions of phosphorus were further studied in sand, silt and clay fractions of these soils and it is observed that aluminium and iron bound phosphorus increase with decrease in the particles size, while the presence of calcium bound phosphorus is more in Silt plus fine sand fraction as coma pared to clay fraction.